CURRENT STATE AND PROSPECTS OF GIS EDUCATION IN KAZNU BY AL-FARABY (Journal of Geography and Environmental Management, 2016)
This article discusses the main directions of development of GIS - Technology at the Faculty of Geography in education and scientific research purposes, as one of the most advanced tools of spatial organization of the data. It is shown that the use of GIS for geo-mapping and the weather forecast is promising for the faculty.